Photoacoustic signal characterization of cell morphology in microchannel flow - Uluç, Nasire. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
Photoacoustic (PA) imaging, a hybrid imaging modality, provides both functional and structural information of biological tissue by combining both optical imaging and ultrasound imaging. It takes advantages of high contrast and resolution, as well as deep tissue penetration. Photoacoustic measurements of biological cells have been used to characterize the cell morphology and allow for the detection of various enzymes activity in vivo and in vitro. In this thesis, I extend the photoacoustic transport model for the examination of detecting red blood cell (RBC) aggregation. To conﬁrm the theoretical predictions, the experiments are conducted by measuring the interaction force between red blood cells via optic tweezers and obtaining photoacoustic signals originating from the blood suspensions. This hybrid simulation approach is for not only the characterization of red blood cell morphology but also for cancer cell lines in the microchannel ﬂow. The activated probe by matrix metalloproteinase (MMP) and melanin-containing which are helpful for the identiﬁcation of cancer cells are detected in a novel design of microchannels in vitro by using photoacoustic microscopy. Moreover, the laser source used in the ﬁeld of photoacoustics is developed in terms of ﬂexibility of adjusting pulse duration (5-10 ns), energy (up to 10 µJ), repetition frequency (up to 1 MHz) independently, and wavelength (from 450 to 1100 nm). Regarding the adjustable properties of the ﬁber laser, the photoacoustic signal is enhanced via bubble dynamics formed under CW irradiation with the help of an analytic model including laser parameters. As a result, the hybrid PAM and OT system can be used for detecting RBC aggregation. Our theoretical simulations show that PA measurements can be used to diﬀerentiate levels of RBC aggregation. Moreover, the expression levels of MMPs in cancer cell lines is determined by combining multi-modality data such as PAM, confocal, and acoustic microscopy.
Keywords: Image processing.; Optoacoustic spectroscopy.